2001
DOI: 10.1080/17450390109386197
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of phytate in the gut of pigs ‐ pathway of gastrointestinal inositol phosphate hydrolysis and enzymes involved

Abstract: The present study gives an overview on the whole mechanism of phytate degradation in the gut and the enzymes involved. Based on the similarity of the human and pigs gut, the study was carried out in pigs as model for humans. To differentiate between intrinsic feed phytases and endogenous phytases hydrolysing phytate in the gut, two diets, one high (control diet) and the other one very low in intrinsic feed phytases (phytase inactivated diet) were applied. In the chyme of stomach, small intestine and colon inos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
112
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 24 publications
20
112
1
Order By: Relevance
“…The AID of DM was approximately 20% units lower than ATTD Cr of DM showing that the DM metabolism proceeds after the small intestine. InsP 6 was not present in ileal digesta of fermented liquid fed pigs, whereas the ileal concentration of InsP 6 -P in pigs fed the three dry diets was closely related to the dietary phytase activity, which agrees with other dry feeding studies (Jongbloed et al, 1992;Skoglund et al, 1997b;Kemme et al, 1999 andRapp et al, 2001;Schlemmer et al, 2001). Consequently, AID and ATTD of P were greatest for pigs fed the fermented diet (diet 4) followed by diets 3, 1 and 2.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The AID of DM was approximately 20% units lower than ATTD Cr of DM showing that the DM metabolism proceeds after the small intestine. InsP 6 was not present in ileal digesta of fermented liquid fed pigs, whereas the ileal concentration of InsP 6 -P in pigs fed the three dry diets was closely related to the dietary phytase activity, which agrees with other dry feeding studies (Jongbloed et al, 1992;Skoglund et al, 1997b;Kemme et al, 1999 andRapp et al, 2001;Schlemmer et al, 2001). Consequently, AID and ATTD of P were greatest for pigs fed the fermented diet (diet 4) followed by diets 3, 1 and 2.…”
Section: Discussionsupporting
confidence: 79%
“…Consequently, AID and ATTD of P were greatest for pigs fed the fermented diet (diet 4) followed by diets 3, 1 and 2. The negative impact of heat-treatment on AID and ATTD of P is in the range of earlier studies, where wheat or barley dominated diets were steam-pelleted at 808C to 1208C (Jongbloed and Kemme, 1990;Skoglund et al, 1997b;Vande Ginste and De Schrijvert, 1998;Schlemmer et al, 2001). The positive impact of fermentation on AID and ATTD of P is in line with results by Lyberg et al (2006) using a non-heat-treated wheat/barley-based diet (fermented for 23.5 h at room temperature with 50% residual in the tank).…”
Section: Discussionmentioning
confidence: 73%
“…First, the response of digestible P (Table 2) confirms that a considerable portion of dietary PP, namely 20 6 6.1% (P , 0.001), is available for absorption without any exogenous phytase supply (Jongbloed et al, 1992;Rapp et al, 2001;Kemme et al, 2006). Indeed, PP hydrolysis may be achieved by means of microbes such as lactic acid bacteria in the stomach (Shirai et al, 1994;Sreeramulu et al, 1996), traces of activity remaining from feedstuffs and alkaline phosphatase activity in the small intestine (Schlemmer et al, 2001). Furthermore, the model indicates that PhytP and PhytM supply improves digestible P to different extents.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown in pigs and chickens ) that the total tract phytate degradation was not related to the level of endogenous phytase in the diet. On the contrary, Schlemmer et al (2001) concluded that plant phytases were responsible for the degradation of inositol phosphates in the pig stomach and Oloffs et al (2000) reported a significant correlation between intrinsic phytase activity of feedstuffs and phosphorus utilization in hens. According to Pallauf and Rimbach (1997), the utilization of phytate phosphorus can be considerably increased by feed components such as rye, triticale, wheat and barley, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This method is inaccurate when this activity is measured in samples containing water-soluble phosphates because the high background of P decreases the colour contribution by the enzymatic hydrolysis of phytate. To avoid this problem, Schlemmer et al (2001) elaborated a method based on phytase protein precipitation and subsequent removal of inorganic phosphate by dialysis. An improved colourimetric method for the rapid determination of phytase activity in feeds was developed by Kim and Lei (2005).…”
Section: Introductionmentioning
confidence: 99%